Preserved Burbot Specimen, Dorsal View, Barbells ... : Burbot - Barbels Top View ... - University Of Alberta, Department Of Biological Sciences (University of Alberta Library, 2018)
This is an image of the barbells of a Burbot Specimen. This specimen is observed in Survey of Vertebrates, Zoology 224. This image was created as part of the University of Alberta OER image database project in Biological Sciences. Identifier 2016I. ...